The Rieske FeS protein encoded and synthesized within mitochondria complements a deficiency in the nuclear gene - Golik, Pawel (National Academy of Sciences, 2003)
The Rieske FeS protein, an essential catalytic subunit of the mitochondrial cytochrome bc1 complex, is encoded in yeast by the nuclear gene RIP1, whose deletion leads to a respiratory-deficient phenotype. By using biolistic transformation, we have relocated the nuclear RIP1 gene into mitochondria. To allow its expression within the organelle and to direct its integration downstream of the cox1 gene, we have fused the 3′ end of the Saccharomyces douglasii cox1 gene upstream of the mitochondrial copy of RIP1 (RIP1(m)) flanked by the Saccharomyces cerevisiae cox1 promoter and terminator regions. We show that RIP1(m) integrated between the cox1 and atp8 genes is mitotically stable and expressed, and it complements a deletion of the nuclear gene. Immunodetection experiments demonstrate that the mitochondrial genome containing RIP1(m) is able to produce the Rip1 protein in lower steady-state amounts than the wild type but still sufficient to maintain a functional cytochrome bc1 complex and respiratory competence to a RIP1-deleted strain. Thus, this recombined mitochondrial genome is a fully functional mitochondrial chromosome with an extended gene content. This successful mitochondrial expression of a nuclear gene essential for respiration can be viewed at the evolutionary level as an artificial reversal of evolutionary events.